PEMBELAJARAN MENULIS ARGUMENTASI (STUDI KASUS PADA SISWA SMA MUHAMMADIYAH 1 KARANGANYAR KELAS X ICT) - Nugroho, Sidiq; Setiawan, Budhi; Purwadi, Purwadi (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The aims of this research was: (1) describe the planning of learning to write argumentation, (2) describe the implementation of learning to write argumentation, (3) describe the learning appraisal of argumentation, (4) describe the problems faced in learning to write argumentation, (5) In overcoming the problems encountered in learning to write arguments. This research is a kind of qualitative research with case study approach. The conclusions of this study are as follows. First, the planning of learning to write argumentation consists of syllabus and learning implementation plan. Second, the implementation of learning to write argumentation is quite optimal. Third, the assessment is conducted in two ways: direct and indirect assessment. Fourth, the problems experienced when the implementation of learning took place include: the limited allocation of learning time, the low interest of students, students difficult to pour ideas and ideas into the form of writing, low student vocabulary, and limited facilities and infrastructure. Fourth, the teacher's effort to overcome the problems in the implementation of learning to write argumentation that teachers maximize the delivery of materials, teachers seek a new atmosphere, teachers ask students to create a framework of writing, teachers ask students to make a reading summary, and teachers carry out learning in the language or library laboratory.